Oxidative Stability of Long-Chain Fatty Acids with Different Unsaturation Degrees into Layered Double Hydroxides - Francesca Blasi (Applied Sciences, 2021)
Nowadays, there is increasing evidence that the intake of essential fatty acids (FAs) and oleic acid has high nutritional importance. However, the vulnerability of these FAs to oxidation deserves special attention. FA oxidation may be avoided or delayed by intercalation of its anionic form in inorganic matrices as layered double hydroxides (LDH). Thus, the aim of the study was to evaluate the protective effects of MgAl LDH towards oleate (O), linoleate (L) and α-linolenate (Ln) degradation. The incorporation and the loading of different FAs in anionic form in LDH was determined by X-ray diffraction and thermogravimetric analysis (TGA), respectively. In order to study the selectivity of LDH towards the FA, the inorganic solid was equilibrated with a mixture of O, L and Ln (1:1:1). TGA and gas chromatography showed that Ln was preferentially intercalated. Free FA (FFA) and intercalated FA (IFA) were heated at 40 °C in the dark and then analyzed weekly for a maximum of 42 days. Their oxidative stability was evaluated by monitoring the primary and secondary oxidative compounds. The volatile compounds were determined by solid-phase microextraction, coupled with gas chromatography–mass spectrometry. Peroxide values were higher in FFA samples than in IFA samples, such as hexanal and trans,trans-2,4-heptadienal % contents. The results showed the potential of LDH intercalation for FA preservation from oxidative modification.